The Application of RAMS in Network Control System Designing of Rail Vehicles - TANG Xian-kang; LIU Xiao-bing; TIAN Ya-hua; WANG Wan-lei (机车电传动)
RAMS element relationship, structure and the component functions of the rail vehicle network control system were analyzed. RAMS designing method for network control system was introduced, including availability designing, reliability asigning and predicting, maintainability asigning and predicting method, and maintainability verification. Based on RAMS, a corresponding network control design flow chart was put forward, which improved product design flow chart with contract index satisfied.